2016
DOI: 10.4143/crt.2015.400
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Scoring Index for Patients with Metastatic Pancreatic Adenocarcinoma

Abstract: PurposeThis study focused on implementation of a prognostic scoring index based on clinico-laboratory parameters measured routinely on admission in metastatic pancreatic cancer patients.Materials and MethodsRecords from 403 patients of metastatic disease were analyzed retrospectively. Continuous variables were dichotomized according to the normal range or the best cut-off values statistically determined by Contal and O’Quigley method, and then analyzed in association with prognosis—overall survival (OS), using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…There have been a couple of studies investigating the association between HGB and clinical outcomes of PC patients. A previous study showed that HBG was an independent factor for OS of metastatic PDAC patients ( 50 ). In addition, the study by Ruiz-Tovar et al.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a couple of studies investigating the association between HGB and clinical outcomes of PC patients. A previous study showed that HBG was an independent factor for OS of metastatic PDAC patients ( 50 ). In addition, the study by Ruiz-Tovar et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on patients with APC have poorly focused on the prognostic role of inflammatory markers, 1115 or have mainly focused on predicting mortality but not toxicity. 2,3,1618 In addition, there is great heterogeneity across APC studies in the reporting of clinical and laboratory variables and their prognostic impact. 4 In a recent expert consensus document, the main variables considered to be significantly related to prognosis in randomized controlled trials investigating first-line systemic therapy for unresectable pancreatic cancer were albumin, bilirubin, CA 19-9, disease status, performance status, pain at baseline, ALP, lactate dehydrogenase and liver metastasis, while other variables, even if not with unanimous prognostic significance, were suggested to be mandatory and recommended prognostic variables to be reported (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of various prognostic markers has led to the establishment of prognostic indices. Using a combination of five parameters (PS, hemoglobin, leucocyte count, neutrophil-lymphocyte ratio, and CEA), Park et al 127 divided patients with metastatic pancreatic cancer into three risk groups and showed a median overall survival of 11.7, 6.2, and 1.3 months for the low, intermediate, and high-risk groups, respectively (p < 0.001). For patients with advanced disease receiving palliative chemotherapy, a prognostic index model of three clinical parameters (ECOG PS, CA19-9 serum levels, and C-reactive protein (CRP) serum levels) was published by Xue et al The median overall survival for the low-risk and high-risk group was 9.9 and 5.3 months, respectively (p < 0.001) with estimated 1-year survival rates of 40.5% (low-risk group) and 5.9% (high-risk group; p < 0.05).…”
Section: Prognostic Indicesmentioning
confidence: 99%